A Short Review on Aluminium Smelting and Its Future Prospect in Malaysia Metal Industries - Badarulzaman, Nur Azam (International Journal of Integrated Engineering, 2015)
Domestic demand for aluminium had increased during the past several years and expected to grow in the future. Non-ferrous metal like aluminium was important because of desirable properties such as low weight despite the higher cost compared to ferrous metals .The main process in the aluminum industries sector which produce aluminium sheets/foils, aluminium fin stock, aluminium ingots (recycled), aluminium rods and aluminium extruded profiles was come from aluminium smelting process. The non-ferrous metal such as aluminium industries provided linkages mainly in the construction industry, semiconductor industry, transportation industry and packaging industry.